Ionizing radiation induces EphA2 S897 phosphorylation in a MEK/ERK/RSK-dependent manner. (2nd September 2017) - Graves, Paul R.; Din, Shaun U.; Ashamalla, Mark; Ashamalla, Hani; Gilbert, Thomas S. K.; Graves, Lee M.
Abstract: Purpose: The EphA2 tyrosine kinase is frequently overexpressed in human tumors that are also treated with radiation. However, few studies have examined the effect of radiation on the EphA2 receptor itself. The purpose of this project was to investigate the impact of radiation on EphA2 to better understand mechanisms of radioresistance. Materials and methods: Cell lines were exposed to X-rays and assayed for changes in EphA2 protein levels and phosphorylation over time by Western blotting. HEK293 cells stably expressing wild-type EphA2 or the S897A mutant were analyzed for cell survival from X-rays. Results: Treatment of different cancer cell lines with 2 Gy of X-rays induced the phosphorylation of EphA2 on S897 but no changes were found in EphA2 total levels or its tyrosine phosphorylation. Radiation-induced S897 phosphorylation was unaffected by an AKT inhibitor but blocked by a MEK or RSK inhibitor. HEK293 cells expressing the EphA2 S897A mutant had a nearly 2-fold lower level of cell survival from X-rays than cells expressing wild-type EphA2. Conclusions: These findings show that radiation induces S897 EphA2 phosphorylation, an event associated with increased cell survival. Therefore, targeting pathways that mediate EphA2 S897 phosphorylation may be a beneficial strategy to reduce radioresistance.